Awareness about physiotherapy in patients with diabetes: A population-based study - Goyal, Rishabh; Chakraverty, Sneha; Zafar, Shahiduz (International journal of health sciences, 2022)
Background and Purpose: The main purpose of this study is to see the awareness about physiotherapy in people suffering from a diabetic condition in India. Physiotherapy can play a very important role in the life of people with the diabetic condition. Materials & Methods: The participants who visited doctors for diabetic treatment were asked to volunteer in the study. A total of 40 subjects volunteered in the study. All were informed about the study and data collection was made in google form. Results: By result shows very little awareness in a diabetic patient about physiotherapy and its benefit in the condition. Conclusion: Therefore, by this study and the above data, we can conclude that there is very little awareness in the people in diabetic condition for the benefit in their life. They don’t know the advantages of physiotherapy in diabetic conditions and the effects on ROM and their quality of life and pain. Awareness needs to be created in the Indian population about the effects of physiotherapy in diabetic patients and its benefits in their life.